Psycho-emotional characteristics that facilitate smoking cessation - Renata , M. David (International Journal of Psychosocial Rehabilitation, 2016)
Objectives: To investigate and clarify which psycho-emotional factors are related to success in smoking cessation. Results: Of the 65 individuals who participated in the study, 36 were successful in smoking cessation. There was an association between the level of addiction to nicotine and an unsuccessful outcome in smoking cessation (p = 0.009). It was also observed that failure in smoking cessation was associated with both the presence of depressive episodes (p = 0.037) but also of severe psycho-emotional disorders (p <.001). In the binary logistic regression analysis for the psycho-emotional disorders and relapse chances in Group Success there was no statistical significance (p> 0.05) in all the variables studied. Conclusion: Among the factors related to failure in smoking cessation, the presence of severe psycho-emotional and current untreated alcoholism should be highlighted. The factors related to successful cessation were the absence of alcoholism and lower levels of dependence on nicotine.